2021
DOI: 10.3390/ijms222413405
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic Anhydrase IX Inhibitors as Candidates for Combination Therapy of Solid Tumors

Abstract: Combination therapy is becoming imperative for the treatment of many cancers, as it provides a higher chance of avoiding drug resistance and tumor recurrence. Among the resistance-conferring factors, the tumor microenvironment plays a major role, and therefore, represents a viable target for adjuvant therapeutic agents. Thus, hypoxia and extracellular acidosis are known to select for the most aggressive and resilient phenotypes and build poorly responsive regions of the tumor mass. Carbonic anhydrase (CA, EC 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 105 publications
1
27
0
Order By: Relevance
“…Various combinations of CA-inhibitors have been described in the literature. The majority of them exhibited synergic activity in cancer cells as described in 204 . Moreover, antibodies targeting CAIX and CAXII have been developed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Various combinations of CA-inhibitors have been described in the literature. The majority of them exhibited synergic activity in cancer cells as described in 204 . Moreover, antibodies targeting CAIX and CAXII have been developed.…”
Section: Discussionmentioning
confidence: 98%
“…Thus combination therapies involving various anticancer agents have been shown to exhibit profound antitumor efficiency when used with CAIX/CAXII inhibitors 90 , 111 , 159–161 . This topic has been recently reviewed in 204 .…”
Section: Combination Therapies Synthetic Lethality and Multitargeting...mentioning
confidence: 99%
“…However, CA IX is also implicated in the development of drug resistance [ 6 , 35 ]. In order to avoid the possible drug resistance and/or to improve its cytotoxic efficacy, attempts have been made to study the effects of CA IX inhibitors in combination with conventional chemotherapy [ 42 , 43 , 44 ]. For instance, in vitro preclinical studies demonstrated that SLC-0111 complemented and potentiated the cytotoxic effects of conventional chemotherapeutic drugs, including dacarbazine and temozolomide in A375-M6 melanoma cells, DOX in MCF-7 breast cancer cells, and 5-fluorouracil in HCT116 colorectal cancer cells [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been borne out in a number of in vitro and in vivo tumor models. Combining CAIX inhibitors with standard of care chemotherapy agents has been demonstrated to be significantly more efficacious than single agents alone [ 38 , 39 , 40 ]. Thus, combining the CAIX inhibitor, SLC-0111 with paclitaxel or with sunitinib in breast cancer [ 19 , 41 ], with temozolomide in pediatric and adult glioblastoma [ 42 ], with gemicitabine in pancreatic cancer [ 43 ], or an analog of SLC-0111, FC531, with cytarabine or Quizartinib in acute myeloblastic leukemia (AML) [ 44 ], results in greater inhibition of tumor growth and in significant increases in the survival of the tumor bearing mice.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%